Questões de gênero em jogos digitais: uma coleção de recursos educacionais abertos de apoio à mobilização - Rodrigues, Letícia (2017)
Several groups, such as women, gays, lesbians, bissexuals, transexuals and transgender, have claims of participation in digital games which has generated a scenario of transformations in this community. Part of this movement is due to the way in which certain people have been marginalized and invisible in this environment due to issues of sex/gender, race/ethnicity and other cleavages. These individuals or groups have increasingly claimed, from various strategies, their recognition by industry and sympathetic communities, and/or even by the communities in which they play. This research discusses gender issues within the context of digital games from the perspective of gender studies and feminism. I seek to reflect on the activity of playing through the concept of technologies of gender through which specific gender relations are often reiterated or even forged, considering how these games are often developed (division of labor), disclosed (patterns Heteronormative, Eurocentric, etc.) or experienced (chauvinism, misogyny, racism, and other prejudices). Through this research I present the prototype of an open collection in Zotero that aims to facilitate the access and circulation of resources that can help in the discussion of gender issues and their intersectionalities. By means of this prototype, the structure of a future collection, in platform yet to be determined, is outlined. I aim that in the future it can be a pedagogical space that promotes the questioning of gender norms and the naturalization of exclusionary practices, whether in the teaching of digital games (undergraduate courses, specialization, etc.), as something to be considered in games development spaces in industry, in the daily practices of players, and/or in the themes of researchers in the area. We emphasize the open character of the collection in the sense of providing future contributions to it, allowing it to be updated in the face of the recurring transformations in the digital games scene in relation to social, cultural and historical dimensions. Such a collection would be the first step in recognizing participants whose invisibility is clear in the area of digital games.